Executive function and its relationship to sensitivity to problems for distinguished and regular students, a comparative study - Muhammad, Maryam Mahzoul (Al-Adab Journal, 2015)
The Current Research Aiming For: 1- Measure Executive Function For Distinguished Students. 2- Measure Executive Function For Ordinary Students. 3- Realizing Differences In Executive Function According To Gender (Males And Females )And Study Kind ( Distinguished And Ordinary ) . 4 -Measure Sensitivity To Problems For Distinguished Students. 5 -Measure Sensitivity To Problems For ordinary Students . 6 -Realizing Differences In Sensitivity To Problems According To Gender (Males And Females) And Study Kind ( Distinguished And Ordinary ) . 7 -Realizing The Relation Between Executive Function And Sensitivity To Problems. To Accomlish Research Goals,The Research Has Ready The Measure Of Executive F unction And The Measure OF Sensitivity To Problems With Their TO Parts(A-B) . 1-Coining (30)Items To Describe Executive Function Distributed As(6)Items On(5)Fields. 2- Coining (12) Behavioral Position To Describe Sensitivity To Problems (A) (Direct Awareness) Distributed As(3) Items On(4)Fields. 3- Choosing (9) Forms To Describe Sensitvity To Problems (B) (Indirect Awareness). Researcher Implemented The Two Measures On Sample Contain (200) Male And Female Secondary Student Distributed As (100)Male And Female From Distinguished Secondary School And (100)Male And Female From Ordinary Secondary School For Grades (Fourth ,Fifth, Sixth)Scientism Specialization For Study Season 2014-2015 .After Processing Data Statistically Using (T-Test)For one Sample And (T-Test) For Two Independent Samples And Pearsons Correlation Coefficient And Point – Biserial Correlation Coefficient And Phi Correlation Coefficient And Chi-quare Test And Alpha – Cronbach Formula And Kuder- Richardson Formula And Two – Way Analysis Of Variance . Research Reached Many Results: 1-Research Sample (Distinguished Students)Has Above Medium Theoretical Measure LevelFor Executive Function . 2-Research Sample( Ordinary Students ) Has Above Medium Theoretical Measure Level For Executive Function. 3-There Is No A Statistical Distinguish Difference In Executive Function According To Gender (Males And Females ) , There Is A Statistical Distinguish Difference According To Study Kind (Distinguished And Ordinary ) For Distinguished Interest , There Is A Reaction Between Gender ( Males And Females) And Study Kind (Distinguished And Ordinary) .4 - Research Sample (Distinguished Students ) Has Above Medium Theoretical Measure Level For Sensitivity Problems. 5 - Research Sample (Ordinary Students ) Has Above Medium Theoretical Measure Level For Sensitivity Problems . 6 – There Is A statistical Distinguish Difference In Sensitivity Problems According To Gender ( males And Females ) For Female Interest , There Is No A statistical Distinguish Difference According To Study Kind (Distinguished And Ordinary ) , There Is No A Reaction Between Gender ( Males And Females) And Study Kind (Distinguished And Ordinary) . 7 - There Is A Positive Relation Between Executive Function And Sensitivity To Problems. According To Research Results , Researcher Came Up With Many Recommendation.1-Ministry Of Education Should Improve Awareness Of Executive Function And Sensitivity To problems And Its Important Active Role In Education Life . And To Complete And Cover The Research , Researcher Suggested: 1-Doing Researches Like The Presence Research , On Other Samples Including Social And Different Segments